ANALISIS TINGKAT KELAYAKAN USAHA UBI KAYU SEBAGAI KOMODITAS UNGGULAN AGRIBISNIS DI KECAMATAN KOLANG KABUPATEN TAPANULI TENGAH - Endang Sari Simanullang; Mitra Musika Lubis (Fakultas Pertanian, Universitas Riau, 2016)
The study attemps to analyze business citeria of cassava as an agribusiness prime commodity in Kolang Districts Tapanuli Tengah Regency. The study using the method of Return Cost Ratio (RCR) analysis. The results show the value of Return Cost Ratio is 2,98. In general, we can confirm that cassava as an agribusiness prime can be developed by farmer. The study is essential for policy decision-making of cassava as an agribusiness prime commodity in Kolang Districts Tapanuli Tengah Regency.